Tight Hamilton cycles in random uniform hypergraphs. Issue 3 (5th February 2012) - Dudek, Andrzej; Frieze, Alan
Abstract In this paper we show that e/n is the sharp threshold for the existence of tight Hamilton cycles in random k ‐uniform hypergraphs, for all k ≥ 4. When k = 3 we show that 1/n is an asymptotic threshold. We also determine thresholds for the existence of other types of Hamilton cycles. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 2013